2022
DOI: 10.18203/2349-2902.isj20221141
|View full text |Cite
|
Sign up to set email alerts
|

A study of preoperative factors predicting a difficult laparoscopic cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy is considered the gold standard treatment for most gallbladder diseases. It has now become one of the most common operations performed by general surgeons. At times, it is difficult and takes longer time or some complications may occur or has to be converted in to open cholecystectomy. This study is undertaken to determine predictive factors for difficult laparoscopic cholecystectomy.  The aim of the study was to study pre-operative factors in the patients to predict wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We found that, impacted stone at the neck of GB is significant factor for predicting a difficult LC (p-0.02) and is consistent with previous studies. [11,12]…”
Section: Discussionmentioning
confidence: 99%
“…We found that, impacted stone at the neck of GB is significant factor for predicting a difficult LC (p-0.02) and is consistent with previous studies. [11,12]…”
Section: Discussionmentioning
confidence: 99%
“…Various problems encountered includes problem in identifying anatomy, anatomical variation, creating pneumoperitoneum, accessing peritoneal cavity, releasing adhesions, fibrotic and contracted gall bladder and extracting the gall bladder. 2…”
mentioning
confidence: 99%